Development of Communication System for UAV Ground Control Station with ATC Based on Controller Pilot Data Link Communication - Kristanto, Andri; Indriyanto, Toto (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2023)
The technology of Unmanned Aerial Vehicles (UAVs), or drones, has rapidly evolved over the years, taking on various missions such as delivery, agriculture, mapping, surveillance, firefighting, and more. With the expanding functions of drones, the operational areas of UAVs also increase. However, there are restricted locations for UAV operations, one of which is an airport. Operating UAVs in controlled airspace requires permission from the government and local regulators. Moreover, a reliable communication system is crucial to support operations and prevent failures. This paper discussed the development of a communication system between UAV Ground Control pilots and Air Traffic Control (ATC) operators. The system utilizes strategic and tactical messages, developing the UAV communication system architecture based on the Controller Pilot Data Link Communication (CPDLC) standard operating procedures. This involved the design of the UAV Ground Control Station (GCS) communication system and the analysis of transmission power. The CPDLC system is a text-based communication system using the internet to send messages to ATC at an airport. The research methods included literature studies, collecting CPDLC messages based on documents (GOLD), developing the UAV communication system architecture, creating strategic communication standard operating procedures, designing the communication system interface on the GCS, and performing power calculations using link budget analysis. The research results indicate that the transmission power, calculated using the link budget at a distance of 100 km, is 17 dBm for payload communication and 15 dBm for telemetry communication, both meeting the minimum link margin standard of 15 dBm.